2015
DOI: 10.3109/21691401.2015.1036998
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic osteogenic tissue formation by MC3T3-E1 cell-laden chitosan/hydroxyapatite composite scaffold

Abstract: This study evaluates the suitability of a macroporous three-dimensional chitosan/hydroxyapatite (CS/HA) composite as a bone tissue engineering scaffold using MC3T3-E1 cells. The CS/HA scaffold was produced by freeze-drying, and characterized by means of SEM and FTIR. In vitro findings demonstrated that CS/HA supported attachment and proliferation of cells, and stimulated extracellular matrix (ECM) production. Tissue biocompatibility and osteogenic capacity of the cell-laden constructs were evaluated in an ecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…This increase in fluorescence at day 8 confirmed that cells are metabolically active and started proliferation inside the pores of scaffolds. Similar results were previously reported by other researchers (Zhang et al 2012;Koç et al 2016). This also shows that the presence of both drugs has no effect towards cell viability as the drug release was continuous and its concentration increased with time.…”
Section: Cell Migration Assaysupporting
confidence: 91%
“…This increase in fluorescence at day 8 confirmed that cells are metabolically active and started proliferation inside the pores of scaffolds. Similar results were previously reported by other researchers (Zhang et al 2012;Koç et al 2016). This also shows that the presence of both drugs has no effect towards cell viability as the drug release was continuous and its concentration increased with time.…”
Section: Cell Migration Assaysupporting
confidence: 91%
“…There are conflicting reports on ideal pore size . The optimal pore size is generally considered to be above 100 μm for inducing bone growth and about 300 μm for bone formation and vascularization . In this study, the pore size and size distribution of the composite scaffolds were evaluated by MIP and SEM analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Particulate HAp can have a highly porous structure, and its fibers can be electrospun and compounded with or without polymers to engineer scaffolds [20,32]. The influence of the Hap-based fabric on the differentiation of mesodermal lineage cell types such as osteocytes has been described [31][32][33]. Earlier studies demonstrated enhanced differentiation, supported attachment, and proliferation, and stimulated extracellular matrix (ECM) production [31,33].…”
Section: Discussionmentioning
confidence: 99%
“…HAp is the main mineral component of mammalian hard tissues (teeth and bones) and human renal calculi [ 30 ]. Particulate HAp can have a highly porous structure, and its fibers can be electrospun and compounded with or without polymers to engineer scaffolds [ 20 , 32 ]. The influence of the Hap-based fabric on the differentiation of mesodermal lineage cell types such as osteocytes has been described [ 31 – 33 ].…”
Section: Main Textmentioning
confidence: 99%